High-throughput microsatellite analysis using fluorescent dUTPs for high-resolution genetic mapping of the mouse genome. - Rhodes, M; Dearlove, A; Straw, R; Fernando, S; Evans, A; Greener, M; Lacey, T; Kelly, M; Gibson, K; Brown, S D; Mundy, C

(untitled) (Genome Research, 1997)
The use of fluorescent end-labeled primers has proved successful for rapid, semiautomated genotyping of microsatellite loci. However, custom synthesis is expensive and costs can be prohibitive when a wide range of markers is to be analyzed for only a few genotypings. This particularly applies to high-resolution genetic mapping in the mouse either in the construction of global maps or in the production of local high-resolution genetic maps for positional cloning. We demonstrate here the use of fluorescent dUTPs for cost-effective, high-throughput microsatellite genotyping in the mouse. This alternative to the use of fluorescent end-labeled primers for semiautomated genotyping is potentially applicable to the construction of linkage maps in other species.